Zinc-Mediated Asymmetric Allylation of Chiral N-tert-Butanesulfinyl Aldimines with 3-Bromomethyl-5H-furan-2-one - Shen, An; He, Zhi-Tao; Yu, Hong-Jie; Fukui, Yuki; Tian, Ping; Lin, Guo-Qiang (Synlett, 2013)
The zinc-mediated asymmetric allylation of chiral N-tert-butanesulfinyl aldimines with 3-bromomethyl-5H-furan-2-one proceeded in good anti/syn selectivities, providing optically pure substituted α-methylene-γ-butyrolactones bearing chiral amine with moderate to excellent yields (28–92%) and diastereoselectivities (76% to >99% de).
Keywords: zinc; diastereoselective; asymmetric allylation; chiral aldimines; α-methylene-γ-butyrolactones